Were Columbaria Used in Judah during the Late Iron Age? - Regev, Dalit (Images in Transition, 2024)
An excavation in a farmstead near Jerusalem exposed several underground installations, of which the most noteworthy is a columbarium dated to the late Iron Age. While columbaria are traditionally dated in the Southern Levant to the Hellenistic period, a few columbaria excavated in the Jerusalem area have unearthed much earlier evidence. How old is the columbaria phenomenon in the Ancient Near East, and should it still be dated to the Hellenistic period?